Europe's Early Fieldscapes
IX, 229 p. 107 illus., 52 illus. in color.
Keywords: This volume focuses on the development of field systems through time and space and in their wider landscape context, including classical issues pertaining to past land use and management regimes, including manuring, water, land and crop management, and technologies such as slash‐and‐burn, ard and plough. This book provides the first comprehensive attempt to bring together and provide a comprehensive insight into the latest prehistoric fieldscape research across Europe. The book raises a broader awareness of some of the main questions and scientific requests that are addressed by scholars working in various fieldscapes across Europe. Themes addressed in this book include (a) mapping and understanding field system morphologies at various scales, (b) the extraction of information on social processes from field system morphologies, (c) the relations between field systems and cultural and natural features of their environment, (d) time-depths and temporalities of usage, and (e) specifics of the underlying agricultural systems, with special attention to matters of continuity and resilience and relation to changing practices. The case-studies explore how to best approach such landscapes with traditional and novel methodologies and targeted research in order to enhance our knowledge further. The volume offers inspiration and guidance for the heritage management of fieldscapes heritage – not solely for future scholarly research but foremost to stimulate strategic guidance to frame and support improved protection of evidently vulnerable resources for Europe’s future. This volume is of interest to landscape archaeologists.